Spatial Analysis of Built-Up Land Suitability in Ternate Island - Sihasale, Daniel Anthoni; Latue, Philia Christi; Rakuasa, Heinrich (PT. Riset Press International, 2023)
The population of Ternate City which is increasing every year can certainly cause the need for land as a space for their activities to increase and will lead to a kind of competition to get a suitable space and in accordance with the various interests and needs of the community there. This study aims to spatially analyze the suitability of built-up land on Ternate Island, North Maluku Province. This research uses Spatial Multi Criteria Analysis method using variables of terrain shape, slope, distance from road, distance from river, distance from economic activity center, and disaster prone area of Mount Gamalama. The results showed that 49.12% of the Ternate Island area was in the suitable area, 29.57% of the research area was in the less suitable class and the unsuitable class had an area of 21.31% of the total research area. The results of this study are expected to be a reference and input for the evaluation of the Ternate City RTRW in the future.